Family Burden of Schizophrenic Individuals in Asia: Review - Sheilla Varadhila Peristianto; Subandi Subandi; Muhana Sofiati Utami (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
This review aims to understand the evidence of factors and impacts on the family burden in caretaking families of schizophrenic individuals in Asia. The family burden is a problem commonly found in many families worldwide, especially those of schizophrenic individuals among family members. Schizophrenic individuals portray specific dan severe symptoms, having a particular impact on the caretaking family. Responsibility for taking care of the schizophrenic individual makes the family feel either a subjective or objective burden. As a global issue, the family burden is closely related to the cultural context of each country. Values passed on for generations certainly influence individuals' attitudes and behaviour, including dealing with family burdens. The current review uses the scoping review step to discover psychological models in the family burden of caretaking families of schizophrenic individuals and is limited to Asia only. The inclusion criteria using the Populations, Concept, and Context (PCC framework). Populations for this review are families with schizophrenic family members, the Concept is the family burden or caregiver burden, and the Context is narrowed down to Asian countries. The exclusion criteria are the caregiver of individuals with mental illness, living in countries outside Asia, focusing on relapse models in non-family member schizophrenic individuals, speaking languages other than English and Bahasa Indonesia, and articles issued outside 2000 – 2020. There are five steps of methods in the current scoping review: (1) identifying the research question by PCC, (2) identifying the evidence, (3) study selection, ''charting the data'' (extracting the evidence), (4) data synthesis based on critical issues narratively, and (5) collating, summarizing and reporting the results. The results showed that the family's experience while caring for the schizophrenic individual is related to the family burden. The family burden is physical, psychological, emotional, social experiences, and financial problems that the family goes through because of their responsibility in caring for the schizophrenic individual.